Quantitative measurements of active and passive mechanical properties of adult cardiac myocytes. - Lammerding, J.
Cytoskeletal displacement, mechanical coupling between the cytoskeleton and the extracellular matrix, as well as nuclear mechanics can be independently quantified using novel methods based on high-resolution tracking of cellular structures and receptor bound magnetic beads in response to applied forces. These techniques can be applied to study the interaction between known protein function and specific changes in cellular mechanical properties and their role in cardiac hypertrophy.
Keywords: Active mechanical properties; Adult cardiac myocytes; Cardiac hypertrophy; Cellular structures; Cytoskeletal displacement; Extracellular matrix; Fluorescent cell organelle staining; High-resolution tracking; Local cell stiffness; Local contraction force; Magnetic trap; Mechanical coupling; Passive mechanical properties; Protein function; Quantitative measurement; Receptor bound magnetic beads